Prepare for the implications on campus of concealed carry laws. Issue 3 (July 2015) - Hope, Joan
<x xml:space="preserve">Abstract</x> A number of state legislatures have recently considered — or are currently considering — bills to allow permit holders to carry concealed weapons on college campuses. But many campus safety professionals agree that's a problem.